Penerapan Metode Experiential Learning dengan Permainan untuk Meningkatkan Hasil Belajar Ilmu Pengetahuan Alam Kelas V Paninggahan Solok - Yenni Marjanti (FKIP UNIVERSITAS PAKUAN, 2016)
The research is aimed at improving students’ interest and ability to master the material of “The Influence of Friction Forces on Surface Area and the Influence of Friction Forces on the Smoothness and Rudeness of the Surface Using the Method of “Experiential Learning” with the Modification of Children Game. The research was conducted at SDN 14 Paninggahan Solok. The research was carried out from July until April 2013. This is a classroom action research consisting of two cycles. In each cycle there are planning, doing, observing, and reflecting. The technique employed was descriptive analysis technique and the data collecting tools was documentation. The documents were students’ worksheets, scoring list, and observational sheets. The research result shows that by using the method of experiential learning with the modification of children game, the classroom atmosphere became interesting and it improved the students’ achievement. It was proven by the improvement of test result I before the research was conducted. The average score of the students was 54.4%. at the first cycle, it was 71.3% and 91.9% at the second cycle. Positive activities of the students were also improved. At the first cycle it was 30.29% and it became 92.71% at the second cycle. It can be inferred that the method of experiential learning with the modification of children game can improve students’ achievement on natural science subject.